Pengaruh Sikap dan Norma Subyektif Terhadapt Niat Nasabah Dalam Memilih Kredit Tanpa Agunan Pada Bank Permata Cabang Denpasar - Witnyana, Ida Bagus Gede; Sudiksa, Ida Bagus (E-Jurnal Manajemen, 2014)
This study aims to determine the effect of attitude and subjective norm on the intention of customers in choosing a bank loan without collateral In Permata bank Branch Denpasar. The number of samples is determined by the formula Slovin study using purposive sampling as many as 100 customers. Data collected by the method of observation, interviews, documentation and questionnaire, further analysis of the data using multiple linear regression analysis, the classical assumption test, F-test, t-test and Standarized Beta Coefficients. The analysis showed that the attitude and subjective norm and significant positive effect on the intention of customers simultaneously in choosing unsecured loan with Permata Bank Branch Denpasar. Based on the conclusions, the suggestions you can give is to add various products that quarter flowers lighter and longer repayment period specifically to provide more options for customers from various segments according to the condition of the economy, improve the quality of services, particularly related to credit granting process and improve communication marketing through marketing energies in an effort to convince customers. Keywords: attitudes, subjective norms, intentions choosing credit.